Case Report: Combined Small Cell Lung Carcinoma With Pulmonary Adenocarcinoma - Shen, Cheng; Che, Guowei (Frontiers in Surgery, 2022)
Background: CSCLC (Combined small cell lung carcinoma) is defined as cancer tissues that mainly contain SCLC (Small cell lung cancer) components with non-SCLC histopathological types. The most common part of NSCLC (Non-small cell lung cancer) is squamous cell carcinoma or large cell carcinoma. CSCLC contains adenocarcinoma is extremely rare. Case presentation: We report a case with surgically treated diagnosed as CSCLC with adenocarcinoma in an elderly and we summarized the clinical features of this disease. The patient has remained well for over 2 weeks after the treatment. Conclusion: There are still few research reports on CSCLC. Since the survival time of patients with advanced CSCLC is shorter than that of simple SCLC, the recommended treatment for CSCLC is early detection and early surgery. In order to facilitate preoperative diagnosis and avoid misdiagnosis of such rare diseases, more cases need to be reported.